2018
DOI: 10.3233/jad-170159
|View full text |Cite
|
Sign up to set email alerts
|

A Free Radical-Generating System Regulates Amyloid Oligomers: Involvement of Cathepsin B

Abstract: Amyloid-␤ (A␤), a major component of senile plaques, is generated via the proteolysis of amyloid-␤ protein precursor (A␤PP). This cleavage also produces A␤PP fragment-derived oligomers which can be highly neurotoxic. A␤PP metabolism/processing is affected by many factors, one of which is oxidative stress (OS). Associated with aging, OS is an important risk factor for Alzheimer's disease. In addition, the protein degradation systems, especially those involving cathepsins, are impaired in aging brains. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Recent research has demonstrated that APP degraded by lysosomal system (Hein et al, 2017). CTSB is a most abundant cysteine protease with potentially specific roles that cleaves APP and also degrades the Aβ42 peptide (Llorente et al, 2018) in the endo-lysosome system. Lysosomes are ubiquitous organelles that constitute the primary degradative compartments of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that APP degraded by lysosomal system (Hein et al, 2017). CTSB is a most abundant cysteine protease with potentially specific roles that cleaves APP and also degrades the Aβ42 peptide (Llorente et al, 2018) in the endo-lysosome system. Lysosomes are ubiquitous organelles that constitute the primary degradative compartments of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Since APP processing is central to AD pathogenesis, the mechanisms linking OS to APP proteolysis could offer therapeutic targets. Our group previously reported the involvement of OS in APP processing [1], the connection between APP proteolysis and the lysosome system in response to OS [3], and the role of the lysosomal protease CTSB in the accumulation of Aβ oligomers in response to OS [28].…”
Section: Role Of Mmp14 In Ipsc-derived Human Neural Cellsmentioning
confidence: 99%
“…Expression is shown as the fold change after X-XOD treatment compared to control cells at 24 and 36 h. In bold, p < 0:01. (c) SK-N-MC cells were treated with X-XOD for 24 h and then fractionated by differential centrifugation as described in [28]. Western blotting was performed using anti-APP (22C11), anti-MMP14, anti-LAMP1, anti-Rab7, anti-CTSB, anti-EEA1, and anti-GAPDH antibodies.…”
Section: Oxidative Stress Provokes the Accumulation Of An App N-termimentioning
confidence: 99%
“…However, the mild oxidative stress generated by X/XO addition causes a reduction in beta-secretase activity and consequently the level of the amyloidogenic protein Aβ [57]. This protective role of the X/XO system is due to a partial inhibition of cathepsin B, which possess a beta-secretase activity [58].…”
Section: In Vitro Experimentsmentioning
confidence: 99%